KONSISTENSI KEBIJAKAN KANTOR PERTANAHAN DALAM MENSEJAHTERAKAN PETANI MISKIN - Haryo Budhiawan; Aristiono Nugroho (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2014)
To make poor inhabitants obtain welfare is a joint effort of various institutions together with the poor themselves.The task will fail if the interanalisation of interest does not exist. The poor farmers’ welfare is not only the interest of the farmersthemselves but should also be the interest of the land office. This will result if the land office is consistent in empowering thefarmers. What kind of consistency does the land office own at present? The reply can be obtain through a qualitative rationalisticresearch. All of the answers were done through interniews of the informants and library study. The forms of consistency of theland office were defending the opinions, seeking for the funds, and persuading people..The forms of consistency found in villagegovernment the efforts of the village head on preserving the environment. For the poor, the consistency they wanted was thattheir certificates of land ownership to be used as an asset for their future business.Key words: consistency, policy, farmers’ welfare